Developing a Comprehensive Framework for Socio-Environmental and Educational Support to Enhance Student Learning - , Jalal Deen Careemdeen (Archives of Current Research International, 2024)
Aims: This research aims to comprehensively explore the intricate concepts surrounding Socio-Environmental and Educational Support for student learning. Grounded in an extensive analysis of open-access databases, the study leverages reputable platforms such as Sage Journals, Scopus, Google Scholar, ERIC, JSTOR, Emerald, Science Direct, SpringerLink, Taylor and Francis, and DOAJ to provide an overarching perspective on socio-environmental and educational support. Study Design, Place, and Duration: Utilising strategically crafted keywords, the investigation delves into pivotal dimensions of socio-environmental and socio-educational support within student learning. Conceptually framed within Bronfenbrenner's socio-ecological theory (1979, 1995), the study synthesises secondary data and contemporaneous literature reviews from diverse perspectives. The research proposes a nuanced framework with four integral components—home environmental support, school environmental support (including teacher and peer support), community support, and virtual environmental support. Methodology: The research adopts a comprehensive approach, synthesising secondary data and contemporaneous literature reviews. Employing Bronfenbrenner's socio-ecological theory as a conceptual framework, the study utilises strategically crafted keywords to explore pivotal dimensions of socio-environmental and socio-educational support for student learning. A systematic review of 158 studies closely aligned with the core theme was conducted, incorporating both published and unpublished sources. The grey literature technique was employed to enhance the study's robustness, allowing for in-depth analysis and conceptualisation of insights not readily available in commercial publications. Results: The research comprehensively explains the dynamic interplay between socio-environmental factors and educational support in optimising student learning experiences. The proposed framework, encompassing home environmental support, school environmental support (including teacher and peer support), community support, and virtual environmental support, offers a nuanced perspective on effective strategies for fostering an environment conducive to student learning. Conclusion: In conclusion, this study thoroughly explores Socio-Environmental and Educational Support for student learning. By embracing diverse sources and employing a systematic approach, the research offers valuable insights into the complex interrelationships among socio-environmental factors, educational support, and student learning experiences. The proposed framework serves as a foundation for future discussions and the development of effective strategies to enhance the learning environment for students.